Autorteksts kā nacionālā korpusa un rakstnieka valodas vārdnīcas resurss - Baltiņa, Maija; Vucāne, Daina (Baltistica, 2012)
AUTHOR’S TEXT AS A RESOURCE FOR THE NATIONAL CORPUS AND THE WRITER’S LANGUAGE DICTIONARYSummaryA dictionary of a writer’s language is a vocabulary that has been methodically collected, analyzed and commented upon and represents the language as used by a particular author. The existence of such dictionaries indicates the level of the specific cultural environment, the stage of development of humanities and the capacity of computer resources.In the first stage of the project, the corpus of the writer’s language is created by collecting all the necessary texts of a selected author in a digital form. In the second stage, linguistic analysis of the corpus of the writer’s language is carried out using the existing and improved technologies (software and software tools). And, finally, in the third stage, on the basis of the corpus of the writer’s language a dictionary of the writer’s language is created according to set thematic, philological and stylistic intentions. The analysis is carried out on three levels: computational linguistic, philological and cultural semiotic.The computerized environment provides a precise quantitative characterization of the writer’s vocabulary (part of speech, word use, collocations etc.). From the philological point of view, vocabulary is analyzed with the help of software tools that help identify and demonstrate the stylistic characterization of the writer’s language, namely, the writer’s vocabulary and word use (e.g. metaphors, synonyms, similes etc.). Another benefit of computerized analysis is related to the intention to acquire a more complete and comprehensive idea about specific features of the writer’s language style.